2020
DOI: 10.18678/dtfd.794107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Determinants of Inflation During the COVID-19 Pandemic Period in European Countries: A Spatial Panel Data Analysis

Abstract: Aim: The recent macroeconomic problems in the global economy are highly related to the coronavirus disease 2019 (COVID-19) pandemic. Since the highest spread of the disease is observed in the European countries, it is worthwhile to investigate the macroeconomic indicators in the European Union (EU) member and the candidate countries. Inflation is one of the most important indicators to examine since it may directly affect many macroeconomic variables. In this study, the determinants of inflation in the 28 EU m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
2
12
1
1
Order By: Relevance
“…The authors also pointed the spread of macroeconomic problems such as inflation to neighboring countries. In his study, Cavallo (15) confirms Erdoğan et al (30)'s findings. The author indicated that the COVID-19 inflation rate was higher than the official CPI in the US and there were similar findings for 10 out of 16 sample countries.…”
Section: Impacts On Inflationsupporting
confidence: 75%
See 1 more Smart Citation
“…The authors also pointed the spread of macroeconomic problems such as inflation to neighboring countries. In his study, Cavallo (15) confirms Erdoğan et al (30)'s findings. The author indicated that the COVID-19 inflation rate was higher than the official CPI in the US and there were similar findings for 10 out of 16 sample countries.…”
Section: Impacts On Inflationsupporting
confidence: 75%
“…However, quantitative easing was introduced during the pandemic to alleviate the recession which may result in long-term inflation (29). While there have been low rates of inflation in most of the developed economies, Erdoğan et al (30) indicated that there is increasing pressure on the inflation rates due to increasing domestic money supply and exchange rate variables in developing economies over the pandemic period. The authors also pointed the spread of macroeconomic problems such as inflation to neighboring countries.…”
Section: Impacts On Inflationmentioning
confidence: 99%
“…The examined results unveil that the influence of oil prices is positive and statistically significant on economic growth, inflation, and exports of the country. On the other hand, Erdoğan et al, (2020) illustrates that money supply and exchange rates are the primary factors of increased inflation in the European Union member economies during the Covid-19 pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Providing sufficient healthcare services, economic support, and supplying enough vaccine are mostly related to the macroeconomic stability of local economies. Unfortunately, the pandemic hit the developing countries more than the developed ones not only through lack of the healthcare services but also vulnerable macroeconomic conditions (4,5).…”
Section: Introductionmentioning
confidence: 99%